2014
DOI: 10.1016/j.jor.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection risk following pre-operative MRSA detection in elective orthopaedic surgery

Abstract: Results: 11,567 patients were screened for MRSA. Ninety-nine (0.9%) were colonised and eighty-eight (88.9%) proceeded to surgery. Three patients (3.4%) developed post-operative superficial SSIs. Two were in patients who had total knee replacements (TKR). Conclusion:We conclude that patients should be informed of an increased SSI risk if colonised with MRSA pre-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In a 2014 study, 0.9% of 11,567 elective orthopaedic patients were MRSA colonized with 3.45% of patients undergoing surgery developing postoperative sepsis. 11 Their study demonstrated a similar population size with similar MRSA prevalence but lower rates of surgical infection. This is possibly reflective of lower presurgical infection risk in patients with greater physiological reserve.…”
Section: Discussionmentioning
confidence: 78%
“…In a 2014 study, 0.9% of 11,567 elective orthopaedic patients were MRSA colonized with 3.45% of patients undergoing surgery developing postoperative sepsis. 11 Their study demonstrated a similar population size with similar MRSA prevalence but lower rates of surgical infection. This is possibly reflective of lower presurgical infection risk in patients with greater physiological reserve.…”
Section: Discussionmentioning
confidence: 78%
“…Similar results were seen by Jadrajka et al, Ibtesan et al and Vishal et al, who noted Staphylococcus aureus as the predominant pathogen causing SSI in their studies [ 18 , 25 , 26 ]. Also, it has been shown that about 15–30% of the healthy population carry Staphylococcus aureus in their nares which could opportunistically cause SSI [ 27 ]. In addition, fomites, which include bedsheets have also been proven to be the reservoir of Staphylococcus aureus [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The application of nasal mupirocin to decolonize S. aureus and prevent subsequent SSIs is proven effective in many control studies ( 11 , 13 , 20 , 25 , 26 ). Chen AF et al found that the decolonization protocols using intranasal mupirocin and chlorhexidine washes are effective for reducing MRSA/MSSA colonization ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen AF et al found that the decolonization protocols using intranasal mupirocin and chlorhexidine washes are effective for reducing MRSA/MSSA colonization ( 13 ). Decolonization of S. aureus using intranasal mupirocin and chlorhexidine in patients undergoing elective orthopedic surgery could significantly increase the risk of postoperative SSI ( 11 , 25 ). Agarwala et al ( 20 ) reported that mupirocin was an effective treatment in clearing MRSA from the nares in adult patients undergoing orthopedic surgery in urban India, thereby reducing the incidence of MRSA SSI.…”
Section: Discussionmentioning
confidence: 99%